Clean and Healthy Living Behavior Education to improve the knowledge of Elementary School Students - Dewi Nurhanifah; Muh Ihsan Kamaruddin; Nur Andani (Edukasi Ilmiah Indonesia, 2024)
Clean and healthy living behavior is the main foundation for maintaining individual health and preventing the spread of disease. Education about clean and healthy living behaviors can be done in various ways, such as through counseling, campaigns, the development of educational materials, collaboration with health centers, training, the active role of schools, the use of social media, exemplary examples, and measurement and evaluation. Educational materials that are arranged in an attractive and easy-to-understand manner are the main instruments in this effort. Collaboration with medical personnel, involving health centers, and the active role of schools are recognized as important supporting factors. The use of social media is also integrated as an effective means of reaching a wider audience. By combining these approaches, it is hoped that people can better understand and adopt clean and healthy living behaviors in their daily lives. Evaluation of the effectiveness of educational programs needs to be done to ensure their success and impact on community knowledge and behavior.